Determination of copper in human blood serum by flame atomic absorption spectrometry after UV-assisted Fenton digestion using binary magnetite nanoparticles - Ayyildiz, Merve Firat; Yazici, Elif; Saylan, Meltem; Chormey, Dotse Selali; Bakirdere, Sezgin (ELSEVIER SCI LTD, 2021)
In this study, an effective Fenton digestion procedure based on UV irradiation was used to facilitate copper determination in human blood serum by flame atomic absorption spectrometry. The method was based on the degradation of blood serum samples using free hydroxyl radicals that were generated from the mixture of iron magnetic nanoparticles and hydrogen peroxide under UV irradiation. The digestion procedure was carried out using a simple, multi-functional lab-made UV irradiation reactor. Under the optimal experimental conditions, detection and quantification limits (LOD and LOQ) of the digestion system for copper were found to be 0.15 and 0.51 mg/L, respectively. Different blood serum samples were taken through the optimum procedure to validate the digestion method. Satisfactory percent recoveries (93-107%) were obtained with high repeatability for replicate digestions. This promising digestion method is simple, uses very low sample and reagent volumes, and can therefore be considered as an alternative procedure to microwave digestion.
Keywords: Copper; FAAS; UV-Fenton digestion; Magnetic nanoparticles; Blood serum; FE3O4 NANOPARTICLES; WASTE-WATER; OPTIMIZATION; DEGRADATION; MICROWAVE; REMOVAL; Engineering; Instruments & Instrumentation